BOVINE OOCYTE VITRIFICATION WITH GLASS MICROPIPETES OR OPEN PULLED STRAW - Mezzalira, Alceu; Vieira, Arnaldo Diniz; Cruz, Fabiano Buss; Barbieri, Dilmar Paulo; Damiani, Juliana Cardoso (Revista de Ciências Agroveterinárias, 2002)
To evaluate the effect of different embryo containers in vitrification procedure, oocytes obtained from 2 to 8mm size follicles were randomly allocated in three groups and submitted to maturation in TCM 199 Earle salts medium with 10% of estrus mare serum (SEE), at 39C, with 5% CO2 atmosphere and 95% of relative humidity. After 22 hours of culture, two groups were submitted to a partial remove of cumulus cells by successive pipeting in a maintenance medium (TCM-Hepes + 10% fetal calf serum) and then exposed to an equilibrium solution with 50l of EG and 50l of DMSO in 400l of maintenance medium, for 30 seconds. After that, they were transferred to a vitrification solution composed by 300l of 0.8M sucrose solution in TCM-Hepes with 20% of fetal calf serum, added with 100l of EG and 100l of DMSO, and loaded in groups of five, in glass micropipetes (MV-T1) or pulled straws (OPS-T2) and vitrified. The warming was performed by direct immersion of MV or OPS in a 0.3M Sucrose solution in maintenance medium, at 37 - 38ºC, during five minutes. The oocytes were then transferred to a 0.15M sucrose solution (five minutes) and then to a maintenance medium. Then, the oocytes of both groups returned to the maturation medium for an additional two hours culture period. All groups were then submitted to the same fertilization and culture procedures. Fertilization was performed with 1 x 106 spermatozoa/ml, selected by swim- up procedure, and the incubation of oocytes / spermatozoa was performed in 400l of TALP-FERT medium with 30g/ml of heparin, during 18–22 hours. The culture was performed in SOFaaci. The cleavage rate of 55.5%, 54.6% and 78.6% was observed in the treatments MV, OPS and Control, respectively. The blastocyst rate was 10.0 and 7.9% for the MV and OPS treatments, respectively. There was not significant differences between treatments (p>0.05) and both were inferior (p<0.05) to the Control, 42.8%. These results demonstrated that the glass micropipetes could be used in the bovine oocyte vitrification, providing similar results than those obtained with the OPS.